Effect of peppermint aroma on physiological parameters of mechanically ventilated patients: Randomized placebo controlled trial - Azza Abd Elrazek Baraka (Clinical Epidemiology and Global Health)
Background: Mechanical ventilation increases the stress, anxiety and, the physiological parameters of critically ill patients. Peppermint inhalation reduces the stress and improves physiological parameters in many studies, but none of these studies used peppermint inhalation for mechanically ventilated patients. Objectives: To assess the effect of peppermint aroma on physiological parameters of mechanically ventilated patients. Method: Randomized placebo controlled trial was utilized. This study was conducted at six intensive care units. Conscious patients on mechanical ventilation via endotracheal tube were randomly assigned to two groups. The intervention group received a peppermint inhalation, and the placebo group received water inhalation. Patients in both groups were assessed for their smell ability by the Sniffin Sticks-test before starting the interventions. CONSORT checklist was used to report the study. A total of 52 patients in the intervention group and 54 patients in the placebo group completed the study. Results: The pain score was significantly decreased in the intervention group after starting the intervention in comparison to the placebo group. There was a strong positive correlation between Sniffin Sticks-test score and the decrease in pain score after inhalation of peppermint. Inhalation of mechanically ventilated patients to peppermint decreases pain score. Conclusion: Inhalation of peppermint by mechanically ventilated patients decreases pain scores. The effectiveness of peppermint inhalation is correlated to the smell ability of the patients. So, nurses can use peppermint inhalation to decrease pain in mechanically ventilated patients with Sniffin Sticks test score of 17 or more. Trial registration: The identification number of the registered trial in the Clinical Trials Online Registry is NCT05541809.